Risk factors, changes in serum inflammatory factors, and clinical prevention and control measures for puerperal infection. Issue 3 (28th December 2019) - Song, Hongbi; Hu, Keli; Du, Xuyuan; Zhang, Jiao; Zhao, Shu
Abstract: Background: To investigate the risk factors and changes in serum inflammatory factors in puerperal infection, and propose clinical prevention measures. Methods: A total of 240 subjects with suspected puerperal infection treated in our hospital from January 2017 to December 2017 were collected, among which puerperal infection was definitely diagnosed in 40 cases, and it was excluded in 40 cases. Levels of interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), and high‐sensitivity C‐reactive protein (hs‐CRP) were compared between the two groups, and the change trends of IL‐6 and hs‐CRP were recorded. Results: Levels of IL‐6, hs‐CRP, and TNF‐α in puerperal infection group were higher than those in non‐infection group ( P  < .05). Levels of IL‐6 and hs‐CRP at enrollment and 1‐3 days after enrollment in infection group were higher than those in non‐infection group ( P  < .05). The body mass index >25, placenta previa, placenta accreta, postpartum hemorrhage, premature rupture of membrane, gestational diabetes mellitus, and anemia during pregnancy were relevant and independent risk factors for puerperal infection. Puerperal infection occurred in uterine cavity, vagina, pelvic peritoneum, pelvic tissue, incision, urinary system, etc, and gram‐negative (G+) bacteria were dominated in pathogens. Conclusion: The inflammatory response of patients with puerperal infection is significantly enhanced.